Automated banks' service quality in developing economy: empirical evidences from India. (10th July 2019) - Sadiq, Mohd; Adil, Mohd; Khan, Mohammed Naved
The aim of this study is to examine customers' perceived ' service quality ', ' customer satisfaction ', ' positive word of mouth ' (+WOM) and ' problems encountered ' at automated teller machine (ATMs) of Indian retail banks. It also attempts to propose a modified and refined Parasuraman's SERVQUAL scale relevant for the Indian context as also suggests a comprehensive model for measuring automated service quality at bank ATMs. A structured questionnaire, drawn together from literature, was used to collect data from a total of 219 ATM customers. The proposed refined scale has been tested for dimensionality, reliability, and validity and the research model was tested for validation through structural equation model (SEM) using LISREL 8.50. Research results indicate that expectations of ATM patrons in India were not being fully met. The highest gap score was observed for 'convenience' dimension followed by 'tangibles'. Results also show that service quality and customer satisfaction effect WOM positively and significantly while problems encountered had a negative impact on customer expectations.